2022
DOI: 10.3390/admsci12020066
|View full text |Cite
|
Sign up to set email alerts
|

How Perceived Organizational Support, Identification with Organization and Work Engagement Influence Job Satisfaction: A Gender-Based Perspective

Abstract: The main objective of this study is to analyze the effects of work engagement, identification with an organization and perceived organizational support on job satisfaction and how these issues vary with gender. Data were collected in a public higher education institution with a questionnaire applied to professors and support staff. The data collected from the 171 employees allowed the development of a structural equation model. The results suggest that work engagement constructs have a greater effect on job sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 96 publications
0
26
0
1
Order By: Relevance
“…In this sense, it makes perfect sense for organizations to aim at maximizing and leveraging all their efforts in human resources policies and practices, making their employees aware of this investment and having a very favorable opinion about the support the organization is providing them (Zagenczyk et al 2020). This perception of support is built on the frequency, intensity, and sincerity of organizational expressions of approval, praise, and material and social rewards as a counterpart or result of employees' efforts (Mascarenhas et al 2022). In a different way, Lynch et al (1999) point out that employees can perceive the efforts made by their organization and how available they are to reward their efforts.…”
Section: Perceived Organizational Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, it makes perfect sense for organizations to aim at maximizing and leveraging all their efforts in human resources policies and practices, making their employees aware of this investment and having a very favorable opinion about the support the organization is providing them (Zagenczyk et al 2020). This perception of support is built on the frequency, intensity, and sincerity of organizational expressions of approval, praise, and material and social rewards as a counterpart or result of employees' efforts (Mascarenhas et al 2022). In a different way, Lynch et al (1999) point out that employees can perceive the efforts made by their organization and how available they are to reward their efforts.…”
Section: Perceived Organizational Supportmentioning
confidence: 99%
“…In the same vein, our results provide support for this relationship within a pandemic context. Mascarenhas et al (2022) showed that job involvement was also dependent on the employee's perceived organizational support, especially through expressions of approval and material and social rewards as recognition for employee involvement. Our results align with this study and provide confirmation in pandemic contexts.…”
mentioning
confidence: 99%
“…Previous studies have demonstrated that men and women have different perceived organizational support and turnover intention. 16,44,45 These differences are possibly due to the gender differences projected in employees' working attitudes and behaviors. 16,46 Compared with men, women are more socially oriented and more likely to establish supportive relationships with superiors and coworkers.…”
Section: Perceived Organizational Support Turnover Intentions and Gendermentioning
confidence: 99%
“…The gender (male=0, female=1) was included as a control variable as it may influence perceived organizational support and turnover intention. 26,45,58 Furthermore, this study also includes the above demographic variables considering that education, professional title, the form of employment, marital status, age, organizational tenure, and annual income may also have an impact on turnover intention. [59][60][61][62] Among them, the professional title is a sign reflecting the technical level and working ability of pharmacists.…”
Section: Control Variablesmentioning
confidence: 99%
“…In light of these recent developments in the business world, sales personnel must possess the necessary skills to retain knowledge about their target market, tailor their messages based on the dynamic nature of the situation, collaborate with a diverse range of team members and influence customer perceptions (Kidwell et al, 2021). The necessity of time and changing nature of the selling job, various skills and competencies (Kerr and Marcos-Cuevas, 2022) along with higher levels of work engagement (Mascarenhas et al, 2022) are essential components for salespersons to effectively perform their crucial role in the sales organizations. Mallin et al (2022) advocated that to encounter such changes, organizations should identify and develop specific practices which can enhance and accelerate salespersons' performance and reduce their intentions to leave the organization.…”
Section: Introductionmentioning
confidence: 99%